Older Adults Have Diminished Awareness of Errors in the Laboratory and Daily Life - HARTY, SIOBHAN (My University, 2013)
Poor recognition of the degree or scope of one?s own cognitive deficits is a common feature of many neurological conditions, including diseases of aging, but little is known about the impact the natural aging process has on this aspect of self-awareness (SA). Here, a group of 45 healthy older adults and a comparison group of 45 young adults completed a multidomain assessment of SA. Awareness of daily functioning was evaluated based on discrepancies between self- and informant ratings on questionnaire measures of attentional control, memory functioning, and socioemotional functioning. Online error awareness was also assessed using a variant of the Go/No-Go Error Awareness Task (EAT) in which participants are required to signal commission errors via a separate manual response. While younger participants tended to underestimate their attentional control and memory functioning relative to informant reports, older adults significantly overestimated their abilities. The older adults also exhibited substantially poorer online error awareness compared with young adults, despite the fact that the two groups were matched for overall accuracy. Levels of online error awareness were significantly correlated with discrepancy scores for daily attentional and memory functioning, and with performance of a sustained attention task. These novel findings suggest that an important aspect of the neuropsychology of healthy aging has hitherto been overlooked.
PUBLISHED
Keywords: cognitive aging; self-awareness; error awareness; prefrontal cortex; Sustained attention; Ageing; Neuroscience